Nutritional care in rehabilitation and acute care of stroke patients: a systematic review of clinical practice guidelines - Siewers, Karina; Svaerke, Katrine; Rosenørn, Amira Eliza; Christensen, Hanne (Frontiers in Stroke, 2025)
BackgroundMalnutrition and nutritional care are significant challenges for healthcare professionals treating stroke patients, in both acute care and during rehabilitation. This study aimed to assess and synthesize the nutritional care recommendations in clinical practice guidelines (CPGs) for managing malnutrition risk in stroke patients, evaluate the supporting evidence, identify research gaps, and assess the quality of the CPGs.MethodsThree databases, along with National Medical Association websites and nutrition journals, were searched for CPGs published between 2019 and 2024 that provided recommendations on nutritional care for stroke patients. Two independent reviewers performed data extraction, and three reviewers independently assessed CPG quality and clinical applicability (using AGREE II and AGREE-REX tools).Results13 CPGs were included in this review. These were of varying quality, with overall moderate AGREE II total scores [mean (SD), 55.2% (21.8%)]. Only two CPGs had an overall quality score above 70% based on AGREE-REX total scores, while five were categorized as poor quality (scores < 40%). Most guidelines strongly recommended early dysphagia screening upon hospital admission, including the provision of texture-modified foods for patients with dysphagia. However, recommendations on malnutrition, nutritional support, and supplementation were often either absent or inconsistent across guidelines and recommendations were mostly based on moderate to weak evidence.ConclusionThis study highlights the critical need for more rigorous research, standardized approaches, and patient-centered studies to improve and optimize nutritional care practices for stroke patients.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024498430, PROSPERO registration ID: CRD42024498430.